2021
DOI: 10.1177/09544054211041070
|View full text |Cite
|
Sign up to set email alerts
|

Influence law and optimization analysis of technological parameters of TC4 titanium alloy on water cavitation peening

Abstract: TC4 titanium alloy is widely used in aerospace, petrochemical, pharmaceutical and other fields, which accounts for about 60% of the current titanium alloy products. Water Cavitation Peening (WCP) is a new material surface modification process and has great development potential. The improvement of the water cavitation peening is severely limited by the correlation and coupling between process parameters. Therefore, the influence law of each process parameter is the key problem that needs to be resolved. TC4 ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…However, their proposed models are only reliable when the cavitation pit diameter-to-depth ratio is approximate to 1 which cannot adapt to various situations. Currently, our group [15][16][17] reported a wide application in micro-forming, and a recorded thinning rate as high as 13.6% was obtained. Subsequently, it was found that the graded 2 titanium ultra-thin metallic sheets have complicated deformation and fracture behaviors in the process of water cavitation, which has not been taken seriously by other researchers.…”
Section: Introductionmentioning
confidence: 99%
“…However, their proposed models are only reliable when the cavitation pit diameter-to-depth ratio is approximate to 1 which cannot adapt to various situations. Currently, our group [15][16][17] reported a wide application in micro-forming, and a recorded thinning rate as high as 13.6% was obtained. Subsequently, it was found that the graded 2 titanium ultra-thin metallic sheets have complicated deformation and fracture behaviors in the process of water cavitation, which has not been taken seriously by other researchers.…”
Section: Introductionmentioning
confidence: 99%